Early High Efficacy Treatment in Multiple Sclerosis Is the Best Predictor of Future Disease Activity Over 1 and 2 Years in a Norwegian Population-Based Registry - Simonsen, Cecilia Smith; Flemmen, Heidi Øyen; Broch, Line; Brunborg, Cathrine; Berg-Hansen, Pål; Moen, Stine Marit; Celius, Elisabeth Gulowsen (Frontiers in Neurology, 2021)
BACKGROUND: Moderate and high efficacy disease modifying therapies (DMTs) have a profound effect on disease activity. The current treatment guidelines only recommend high efficacy DMTs for patients with highly active MS. The objective was to examine the impact of initial treatment choice in achieving no evidence of disease activity (NEDA) at year one and year two. METHODS: Using a real-world population-based registry with limited selection bias from the southeast of Norway, we determined how many patients achieved NEDA on moderate and high efficacy DMTs. RESULTS: 68.0% of patients who started a high efficacy DMT as the first drug achieved NEDA at year one and 52.4% at year two as compared to 36.0% and 19.4% of patients who started a moderate efficacy DMT as a first drug. The odds ratio (OR) of achieving NEDA on high efficacy drugs compared to moderate efficacy drugs as a first drug at year one was 3.9 (95% CI 2.4-6.1, p<0.001). The OR for high efficacy DMT as the second drug was 2.5 (95%CI 1.7-3.9, p<0.001), and was not significant for the third drug. Patients with a medium or high risk of disease activity were significantly more likely to achieve NEDA on a high efficacy therapy as a first drug compared to moderate efficacy therapy as a first drug. CONCLUSION: Achieving NEDA at year one and two is significantly more likely in patients on high-efficacy disease modifying therapies than on moderate efficacy therapies, and the first choice of treatment is the most important. The immunomodulatory treatment guidelines should be updated to ensure early, high efficacy therapy for the majority of patients diagnosed with MS.